Educational robotics as a learning aid for disabled children - Valadao, Carlos; Bastos, Teodiano Freire [UNESP]; Bortole, Magdo; Perim, Victor; Celino, Daniel; Rodor, Fauzi; Goncalves, Agda; Ferasoli, Humberto (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Severe disabled children have little chance of environmental and social exploration and discovery, and due this lack of interaction and independency, it may lead to an idea that they are unable to do anything by themselves. This idea is called learned helplessness and is very negative for the child cognitive development and social development as well. With this entire situation it is very likely that the self-steam and mood of this child. Trying to help these children on this situation, educational robotics can offer and aid, once it can give them a certain degree of independency in exploration of environment. The system developed in this work allows the child to transmit the commands to a robot. Sensors placed on the child's body can obtain information from head movement or muscle pulses to command the robot to carry the tasks. Also, this system can be used with a variety of robots, being necessary just a previous configuration. It is expected that, with the usage of this system, the disabled children have a better cognitive development and social interaction, balancing in a certain way, the negative effects of their disabilities. © 2011 IEEE.
Keywords: cognitive development; disabled children; educational robotics; learned helplessness; learning aid; Cognitive development; Disabled children; Economic and social effects; Robotics; Robots; Handicapped persons